Genomic comparison of two strains of Mycobacterium avium subsp. paratuberculosis with contrasting pathogenic phenotype. (January 2023) - Colombatti Olivieri, M.A.; Fresia, P.; Graña, M.; Cuerda, M.X.; Nagel, A.; Alvarado Pinedo, F.; Romano, M.I.; Caimi, K.; Berná, L.; Santangelo, M.P.
Abstract: In a previous study, we evaluated the degree of virulence of Mycobacterium avium subsp. paratuberculosis (Map) strains isolated from cattle in Argentina in a murine model. This assay allowed us to differentiate between high-virulent MapARG1347 and low-virulent MapARG1543 strains. To corroborate whether the differences in virulence could be attributed to genetic differences between the strains, we performed Whole Genome Sequencing and compared the genomes and gene content between them and determined the differences related to the reference strain MapK10. We found 233 SNPs/INDELS in one or both strains relative to Map K10. The two strains share most of the variations, but we found 15 mutations present in only one of the strains. Considering NS-SNP/INDELS that produced a severe effect in the coding sequence, we focus the analysis on four predicted proteins, putatively related to virulence. Survival of MapARG1347 strain in bMDM was higher than MapARG1543 and was more resistant to acidic pH and H2 O2 stresses than MapK10. The genomic differences between the two strains found in genes MAP1203 (a putative peptidoglycan hydrolase), MAP0403 (a putative serine protease) MAP1003c (a member of the PE-PPE family) and MAP4152 (a putative mycofactocin binding protein) could contribute to explain the contrasting phenotype previously observed in mice models. Highlights: WGS of Argentinian isolates with contrasting pathogenic phenotypes. Phylogenetic analysis with whole genome sequences available from GenBank. Identification of NS-SNP and INDELS by comparative genomic analysis.